The IInfluence of the Learning Tournament Strategy on Reading Skills in Observation Results Report Text - Sinsin Nurhaliza; Asep Firdaus; Fauziah Suparman (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The purpose of this study was to determine the effect of the Learning Tournament Strategy on the reading comprehension skills of observational report texts at SMP Negeri 5 Kota Sukabumi in the 2025/2026 Academic Year by paying attention to students’ reading comprehension skills before and after the implementation of the Learning Tournament learning strategy. The duration of the study was five months calculated from November 2025 to April 2026 using a true experimental pretest-posttest design. The research target was class VIII at SMP Negeri 5 Kota Sukabumi in the 2025/2026 Academic Year. Researchers used cluster sampling to determine the sample for each group. Class VIII-B as the experimental group and class VIII-C as the control group, while the research instruments used were written pretest and posttest tests. Based on the results of the research conducted by researchers, 36 experimental group data and 30 control group data were obtained, researchers used the Wilcoxon Test in analyzing the research data. The results of the Wilcoxon test show that the initial ability of students shows that the control class has a reading comprehension ability that is superior to the experimental class, meanwhile after the Learning Tournament strategy is applied, the reading comprehension ability of students in the experimental group can be superior to the control class. The Wilcoxon test also proves that the pretest-posttest results of the experimental group have a significant difference obtained with a significance value of 0.001, in contrast to the pretest-posttest results of the control group which show no significant difference with a significance result of 0.440.